If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + 2x + 7 + -1x + -6x = -3x + -10x + 46 Reorder the terms: -1 + 7 + 2x + -1x + -6x = -3x + -10x + 46 Combine like terms: -1 + 7 = 6 6 + 2x + -1x + -6x = -3x + -10x + 46 Combine like terms: 2x + -1x = 1x 6 + 1x + -6x = -3x + -10x + 46 Combine like terms: 1x + -6x = -5x 6 + -5x = -3x + -10x + 46 Reorder the terms: 6 + -5x = 46 + -3x + -10x Combine like terms: -3x + -10x = -13x 6 + -5x = 46 + -13x Solving 6 + -5x = 46 + -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. 6 + -5x + 13x = 46 + -13x + 13x Combine like terms: -5x + 13x = 8x 6 + 8x = 46 + -13x + 13x Combine like terms: -13x + 13x = 0 6 + 8x = 46 + 0 6 + 8x = 46 Add '-6' to each side of the equation. 6 + -6 + 8x = 46 + -6 Combine like terms: 6 + -6 = 0 0 + 8x = 46 + -6 8x = 46 + -6 Combine like terms: 46 + -6 = 40 8x = 40 Divide each side by '8'. x = 5 Simplifying x = 5
| 86000=x+(x*.46) | | .8m=-96 | | 4(3x-6)=54 | | -2x-(-2x-1)-y=7 | | 8u-(-15)=15 | | 25*x^3+25*x^2-36*x-36=0 | | 5x+15=24x-30 | | 2x+(6x+6)+x=180 | | d+7=7d/3+3/3 | | 16-6.5=9.5 | | d+7=7d+3/3 | | -2x-1(-2x-1)-y=7 | | 11y-7=6y-10 | | 7x+15-6x=-3-10 | | 60*3.5= | | -4h+3+7h=9h-21 | | -8x+3+9x=-11+2 | | -1-9=-4+x | | x+(x*.5)=100 | | x-.5=1.1 | | b+7=3/2b+17 | | 2x^2-4x+y^2-16y=21 | | 0x+y=1 | | 24x=x-5 | | x^2-2x+y^2+4y=20 | | -20=x+4 | | 05x=3 | | 8+11x=28+x | | 12x-7=12x+7 | | 5(c+7)=15(c-3) | | 2x+27+11=4x | | -5x+7x=-6 |